2022
DOI: 10.3847/1538-4365/ac5cbb
|View full text |Cite
|
Sign up to set email alerts
|

New Open-cluster Candidates Found in the Galactic Disk Using Gaia DR2/EDR3 Data

Abstract: We report 541 new open-cluster candidates in Gaia EDR3 through revisiting the cluster results from an earlier analysis of Gaia DR2, which revealed nearly 1000 open-cluster candidates in the solar neighborhood (mostly d <3 kpc) residing at Galactic latitudes ∣b∣ < 20°. A subsequent comparison with lists of known clusters shows a large increase of the cluster samples within 2 kpc from the Sun. We assign membership probabilities to the stars through the open-source pyUPMASK algorithm, and also estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…As such, studies of objects near to the solar system can provide a unique opportunity to obtain more complete cluster samples and richer member information. Based on the Gaia Second Data Release (DR2), since 2018 a large number of nearby star clusters have been identified (Cantat-Gaudin et al 2018), and more new star clusters have been found (e.g., Liu & Pang 2019;Sim et al 2019;Castro-Ginard et al 2020;He et al 2021He et al , 2022. The members of known clusters are constantly updated (e.g., Gao 2018;Monteiro et al 2020;Jaehnig et al 2021;Tarricq et al 2022), and many physical and structural characteristics of these clusters have also been presented (e.g., Cantat-Gaudin et al 2019;Kounkel & Covey 2019;Tian 2020;Zhong et al 2020;Pang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, studies of objects near to the solar system can provide a unique opportunity to obtain more complete cluster samples and richer member information. Based on the Gaia Second Data Release (DR2), since 2018 a large number of nearby star clusters have been identified (Cantat-Gaudin et al 2018), and more new star clusters have been found (e.g., Liu & Pang 2019;Sim et al 2019;Castro-Ginard et al 2020;He et al 2021He et al , 2022. The members of known clusters are constantly updated (e.g., Gao 2018;Monteiro et al 2020;Jaehnig et al 2021;Tarricq et al 2022), and many physical and structural characteristics of these clusters have also been presented (e.g., Cantat-Gaudin et al 2019;Kounkel & Covey 2019;Tian 2020;Zhong et al 2020;Pang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Differently to asterisms or field stars along a given line of sight, the member stars of a cluster have the same characteristics in terms of spatial and kinematic locations; this allows stellar aggregates to be found by clustering based on astrometric data (Castro-Ginard et al 2018;Liu & Pang 2019). Up to now, the majority of new clusters were detected through the DBSCAN clustering algorithm (e.g., Castro-Ginard et al 2020, 2022He et al 2021He et al , 2022 and its improved method HDBSCAN (e.g., Kounkel & Covey 2019;Hunt & Reffert2021). DBSCAN has been demonstrated to be a very efficient blind search method in big-data approaches (Gao et al 2014;Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalogs of OCs have been compiled for over a century (Dreyer 1888). High-quality astrometric and photometric data from Gaia (Gaia Collaboration et al 2016Collaboration et al , 2018Collaboration et al , 2021, combined with new highly efficient tools such as DBSCAN (Ester et al 1996), HDBSCAN (Campello et al 2013;McInnes et al 2017), and UPMASK (Unsupervised Photometric Membership Assignment in Stellar Clusters; Krone-Martins & Moitinho 2014), have dramatically increased the number of OCs (Castro-Ginard et al 2018;Cantat-Gaudin et al 2018;Bica et al 2019;Castro-Ginard et al 2019;Cantat-Gaudin et al 2019;Ferreira et al 2019;Liu & Pang 2019;Sim et al 2019;Castro-Ginard et al 2020;Ferreira et al 2021;He et al 2021;Hunt & Reffert 2021;Qin et al 2021;Castro-Ginard et al 2022;He et al 2022). A complete census of OCs within the solar neighborhood will provide a sound basis to investigate a number of scientific questions.…”
Section: Introductionmentioning
confidence: 99%
“…Catalogs of OCs have been compiled for over a century (Dreyer 1888). High quality astrometric and photometric data from Gaia (Gaia Collaboration et al 2016, 2018, combined with new highly efficient tools such as DBSCAN (Ester et al 1996), HDBSCAN (Campello et al 2013;McInnes et al 2017), UPMASK (Unsupervised Photometric Membership Assignment in Stellar Clusters) (Krone-Martins & Moitinho 2014), have dramatically increased the number of OCs (Cantat-Gaudin et al 2018Castro-Ginard et al 2018Liu & Pang 2019;Sim et al 2019;Bica et al 2019;Ferreira et al 2019Ferreira et al , 2021He et al 2021He et al , 2022Hunt & Reffert 2021;Qin et al 2021). A complete census of OCs within the solar neighborhood will provide a sound basis to investigate a number of scientific questions.…”
Section: Introductionmentioning
confidence: 99%